Reconstructing the Evolutionary History of Chromosomal Races on Islands: A Genome-Wide Analysis of Natural House Mouse Populations. (25th May 2020) - Franchini, Paolo; Kautt, Andreas F; Nater, Alexander; Antonini, Gloria; Castiglia, Riccardo; Meyer, Axel; Solano, Emanuela
Abstract: Chromosomal evolution is widely considered to be an important driver of speciation, as karyotypic reorganization can bring about the establishment of reproductive barriers between incipient species. One textbook example for genetic mechanisms of speciation are large-scale chromosomal rearrangements such as Robertsonian (Rb) fusions, a common class of structural variants that can drastically change the recombination landscape by suppressing crossing-over and influence gene expression by altering regulatory networks. Here, we explore the population structure and demographic patterns of a well-known house mouse Rb system in the Aeolian archipelago in Southern Italy using genome-wide data. By analyzing chromosomal regions characterized by different levels of recombination, we trace the evolutionary history of a set of Rb chromosomes occurring in different geographical locations and test whether chromosomal fusions have a single shared origin or occurred multiple times. Using a combination of phylogenetic and population genetic approaches, we find support for multiple, independent origins of three focal Rb chromosomes. The elucidation of the demographic patterns of the mouse populations within the Aeolian archipelago shows that an interplay between fixation of newly formed Rb chromosomes and hybridization events has contributed to shaping their current karyotypic distribution. Overall, our results illustrate that chromosome structure is much more dynamic than anticipated and emphasize the importance of large-scale chromosomal translocations in speciation.